2000
DOI: 10.1115/1.1413471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reynolds Number and Free-Stream Turbulence on Boundary Layer Transition in a Compressor Cascade

Abstract: An experimental and analytical study has been performed on the effect of Reynolds number and free-stream turbulence on boundary layer transition location on the suction surface of a controlled diffusion airfoil (CDA). The experiments were conducted in a rectilinear cascade facility at Reynolds numbers between 0.7 and 3.0×106 and turbulence intensities from about 0.7 to 4 percent. An oil streak technique and liquid crystal coatings were used to visualize the boundary layer state. For small turbulence levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Experimentally, Leipold et al [6] measured loss and boundary layer parameters in a highly loaded transonic compressor cascade for Reynolds numbers between 300,000 and 1 Â 10 6 . Schreiber et al [7] reported performance dependence of a roughened controlled-diffusion airfoil (CDA) on Reynolds numbers ranging from 100,000 to 3 Â 10 6 . Analytical models to predict performance deterioration of gas turbine compressors have been developed by many researchers including Millsaps et al [8], Aker and Saravanamottoo [9], Massardo [10], Syverud and Bakken [11], and Song et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, Leipold et al [6] measured loss and boundary layer parameters in a highly loaded transonic compressor cascade for Reynolds numbers between 300,000 and 1 Â 10 6 . Schreiber et al [7] reported performance dependence of a roughened controlled-diffusion airfoil (CDA) on Reynolds numbers ranging from 100,000 to 3 Â 10 6 . Analytical models to predict performance deterioration of gas turbine compressors have been developed by many researchers including Millsaps et al [8], Aker and Saravanamottoo [9], Massardo [10], Syverud and Bakken [11], and Song et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…1) There was a good agreement between the test data and the calculated efficiency and performance within Reynolds numbers from 30,000 to 295,000. Schreiber et al 3) researched transition phenomena on the blade surface in a compressor cascade by changing the Reynolds number and turbulence intensity, finding a laminar separation bubble with reattachment on the suction surface at relatively low Reynolds number. Van Treuren et al 4) ran wind tunnel tests at Reynolds numbers from 25,000 to 50,000 and found that a large separation near the trailing edge of a turbine cascade degraded total pressure loss.…”
Section: Introductionmentioning
confidence: 99%
“…For most turbine compressors, the Reynolds numbers based on chord Re c are typically between 0.6 × 10 6 and 4 × 10 6 [9] (the Reynolds numbers based on the leading edge half thickness Re t are typically between 0.3 × 10 4 and 0.9 × 10 4 for aero-engine). The free-stream turbulence intensities (Tu) are around 4% [10] (around 12% when the wake comes).…”
Section: Introductionmentioning
confidence: 99%